Português (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
Abstract: The present work aims to carry out a critical analysis of the limitations imposed by the Brazilian Superior Courts on the knowledge of habeas corpus, its causes and conflicts. As well as synthesizing the decision-making process that accompanied the formalization of these mitigating precedents, as well as their impact on the protection of fundamental rights.Keywords: habeas corpus, higher courts, knowledge, limitation, warranties.